Outcomes Following the Cutting Seton Procedure for High Anal Fistula: Cutting Seton Procedure for High Anal Fistula - Khan, Hasnain; Shah, Farrukh Ozair; Raza, Tilal Ahmed; Mehmood, Ayesha; Khattak, Nouman; Saleem, Ahsan; Abdullah, . (Pakistan Journal of Health Sciences, 2026)
Fistula in ano is a prevalent perianal condition caused by infection of the anal glands between the sphincter muscles, leading to substantial morbidity. It is reportedly more prevalent in males globally. Surgical management of high anal fistula remains challenging, and the cutting seton technique continues to be used as a treatment option. Objective: To evaluate the outcomes following the cutting seton procedure for high anal fistula. Methods: This cohort study was carried out at the Department of General Surgery, Hayatabad Medical Complex, Peshawar, and involved 171 patients who were diagnosed with high anal fistula, and the cutting seton procedure was performed on them. The demographic data, clinical characteristics, and surgical outcomes were documented. The pain was rated with the help of the Visual Analogue Scale (VAS), and recurrence and incontinence were recorded in the course of follow-up. The chi-square test was used, keeping p-value > 0.05 as statistically significant. Results: The mean age of patients was 42.3 ± 11.4 years, with 60.8% being male. Postoperative pain was reported in 55.0% of patients. Recurrence occurred in 12.9%, and incontinence was observed in 18.1%, primarily to flatus. Stratification showed no significant associations between outcomes and demographic or clinical variables (p>0.05 for all). Conclusions: Seton is a safe and efficient intervention in high anal fistula, and results are satisfactory regardless of the demographics of patients and are largely dependent on the surgical approach and fistula features.